PENETAPAN NAFKAH MANTAN ISTRI DALAM MASA IDDAH DI PENGADILAN AGAMA SUNGAI PENUH - Jaka Sandara; Ikhwan Ikhwan (Jurnal AL-AHKAM, 2020)
As  the  purpose  of  marriage  in  Islam,  it  is  not  solely  for  outer  pleasure  but  also  forms  an institution where men and women can guard themselves from error and sinful acts, give birth and care  for  children  to  continue  human  descent  and  fulfill  reasonable  and  necessary  sexual  needs  to create comfort and happiness. In order for the realization of a happy family the husband and wife must fulfill their obligations. One of the husband's obligations is material which is called livelihood, but  in  fact  many  families  end  up  in  divorce  which  results  in  ex-husbands  having  to  fulfill  their obligations  despite  divorce  which  is  called  a  living,  this  must  certainly  be  in  accordance  with Islamic law and law. applicable law, this is where judges are required to decide decisions that are fair  and  not  detrimental  to  both  parties,  this  inquiry  will  discuss  how  judges  decide  the  case  of living in the court of Religion As the purpose of marriage in Islam, not solely for outward pleasure but  also  establish  an  institution  in  which  men  and  women  can  guard  themselves  from  error  and sinful acts, give birth and care for children to continue human descent and fulfill reasonable sexual needs  and  are  needed  to  create  comfort  and  happiness.  In  order  for  the  realization  of  a  happy family  the  husband  and  wife  must  fulfill  their  obligations.  One  of  the  husband's  obligations  is material which is called livelihood, but in fact many families end up in divorce which results in ex- husbands  having  to  fulfill  their  obligations  despite  divorce  which  is  called  a  living,  this  must certainly  be  in  accordance  with  Islamic  law  and  law.  applicable  law,  this  is  where  the  judge  is demanded  to  be  able  to  decide  a  verdict  that  is  fair  and  not  detrimental  to  both  parties,  this questionnaire  will  discuss  how  the  judge  decides  on  the  case  of  living  in  the  religious  court  on  a Sungai PenuhKeyword: iddah, Nafkah, Pengadilan Agama  A.  Pendahuluan